2020
DOI: 10.1093/jjco/hyaa195
|View full text |Cite
|
Sign up to set email alerts
|

Uniform infection screening allowed safe head and neck surgery during the coronavirus disease 2019 pandemic in Japan

Abstract: Background The purpose of this study was to determine whether a uniform infection screening protocol could be used to safely perform head and neck cancer surgery during the coronavirus disease 2019 pandemic and clarify how surgical treatment changed compared with the pre-pandemic period. Materials and methods During the unprecedented coronavirus disease 2019 pandemic in Tokyo, we continued providing head and neck cancer care,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The results of this study are in concordance with the data from most other centres 18 , 19 , which clearly show that the postoperative outcomes remain unchanged with no added risk or a minimal risk of SARS-CoV-2 infections in healthcare personnel. Iyer et al reported that there was a reduction in number of cases (overall operative caseload) to about 60% of the pre-COVID-19 times in order to maintain adequate safety and implement protective measures for COVID-19 transmission 20 .…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study are in concordance with the data from most other centres 18 , 19 , which clearly show that the postoperative outcomes remain unchanged with no added risk or a minimal risk of SARS-CoV-2 infections in healthcare personnel. Iyer et al reported that there was a reduction in number of cases (overall operative caseload) to about 60% of the pre-COVID-19 times in order to maintain adequate safety and implement protective measures for COVID-19 transmission 20 .…”
Section: Discussionsupporting
confidence: 90%
“…40 Performing a preoperative nasopharyngeal swab in all patients with HNC was done to reduce the possibility of perioperative complications and to keep hospitals safe for other patients and staff. [41][42][43] HNCs arise from mucosal membranes and the diagnosis and treatment often involve potential viral exposure, dysphagia or airway compromise, and nasogastric or tracheotomy tubes, all factors potentially exposing health care providers to aerosolized virus. 41,44 In this scenario, social distancing and personal hygiene are mandatory to avoid spread of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, studies have shown that with an appropriate screening process and postoperative care, these elective procedures can be performed safely during the current pandemic while minimizing delays in treatment. [28][29][30][31] Furthermore, it could be then reasonable to infer that due to the massive elective surgeries' cancellations secondary to the COVID-19 pandemic, delays in diagnosis and treatment, as well as a surge of advanced HN cancer are anticipated. [32][33][34] Moreover, Kiong et al, in a retrospective review, evidenced an increased tumor burden in patients with HN malignancies, despite having similar time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, studies have shown that with an appropriate screening process and post-operative care, these elective procedures can be performed safely during the current pandemic while minimizing delays in treatment. [28][29][30][31] This article is protected by copyright. All rights reserved.…”
Section: Accepted Manuscriptmentioning
confidence: 99%